2011
DOI: 10.1111/j.1600-0765.2011.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma calprotectin and polymorphisms of S100A8 in patients with aggressive periodontitis

Abstract: These findings indicate that aggressive periodontitis is associated with elevated levels of plasma calprotectin and that gene polymorphisms of S100A8 may influence the susceptibility and severity of aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 38 publications
4
36
1
Order By: Relevance
“…Previous studies showed that MRP‐8/14 was present in human dental calculus and that its levels in the GCF from patients with periodontitis were higher compared to those from healthy controls and were correlated with clinical and biochemical markers of periodontal inflammation 47 . In contrast to the study by Sun et al, 29 higher serum levels of MRP‐8/14 were correlated not only with PDs but also with the extent of periodontal disease. The significant correlation of salivary and serum MRP‐8/14 in the present study indicates the systemic influence periodontal inflammation exerts on the body.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies showed that MRP‐8/14 was present in human dental calculus and that its levels in the GCF from patients with periodontitis were higher compared to those from healthy controls and were correlated with clinical and biochemical markers of periodontal inflammation 47 . In contrast to the study by Sun et al, 29 higher serum levels of MRP‐8/14 were correlated not only with PDs but also with the extent of periodontal disease. The significant correlation of salivary and serum MRP‐8/14 in the present study indicates the systemic influence periodontal inflammation exerts on the body.…”
Section: Discussionmentioning
confidence: 71%
“…It was suggested that, in periodontal disease, the role of PMNs to clear potentially pathogenic bacteria make it plausible to link periodontal disease activity and elevated levels of MRP‐8/14 27 . MRP‐8/14 release from neutrophils is enhanced by lipopolysaccharides from Porphyromonas gingivalis , Aggregatibacter actinomycetemcomitans , Prevotella intermedia , and Fusobacterium nucleatum , and levels of this peptide are elevated in epithelial tissue and CT and in serum of patients with periodontitis 28 , 29 . MRP‐8/14 also exhibits antimicrobial activity against P. gingivalis in gingival epithelium and has inhibitory effects on macrophages and lymphocytes 7,30‐32 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the potential additional confounding effect of gender differences, we designed the present study to assess the impact of calprotectin only in females undergoing RYGB. In this regard, it is also worthwhile to mention that no significant association was found between calprotectin levels and gender in a study including 139 subjects (30).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a protective role for the S100A8/A9 complex in periodontal diseases, single nucleotide polymorphisms (i.e., SNP rs3795391, A > G) in the S100A8 upstream promoter are associated with increased overall risk of periodontitis [110] and susceptibility to aggressive periodontitis within a family [111] and across a population [112]. The rs3795391, A > G polymorphism is less prevalent in patients with aggressive periodontitis than the AA genotype, although plasma concentrations of S100A8/A9 were similar to patients with SNP rs 3806232 [112]. The copy number of transcripts for the two S100A8 promoter SNPs has not been reported, although differences may be expected.…”
Section: Effector Arm Of Innate Intraepithelial Immunitymentioning
confidence: 99%